Manufacturing Consent Revisted: China’s image in selected South African media in the opening phase of the Covid-19 pandemic: (The Strategic Review for Southern Africa, 2021)
The absence of any real substantial critique of China in South Africa media in the aftermath of Covid-19 is cause of concern given the increasing evidence to suggest that China is exporting its authoritarian press censorship culture abroad. South Africa, a strategic partner of China, offers insight into this “export.” In developing a methodology which asks if “China is crafting its image”, this research examines a sample of South African media between March- July 2020 to ascertain if censorship occurred. Deploying the theoretical framework of the Propaganda Model (PM) developed Herman and Chomsky’s “Manufacturing Consent” theory, the research cross analyzes via five filters to determine if China is “Manufacturing Consent” within the South African media.
Keywords: Propaganda, Manufacturing Consent, Media analysis, South Africa, Covid-19